Adaptation of Local Sweet Potato Clones in tha Lowlands of Papua - Demas Wamaer (Agros Journal of Agriculture Science, 2017)
Objective of study was to obtain local clones of adaptive lowland ubijalar in Papua. Experiment was conducted in lowland dry season 2012/2013 in two locations, namely Keerom and Jayapura districts. Randomized Block Design (RAK), 10 local varieties of adaptive lowland Papua and two national superior varieties (Beta 2 and Cangkuang) were used. Cultivation technique used is a bund system. Results: there were three local varieties with higher yield and yield potential than Beta-2 comparison varieties (22.4 t/ha with yield potential 22.9 t/ha) and Cangkuang (20.6 t/ha with potential yield 21,6 ta/ha), while the three local varieties are Ningkay-3 having average productivity 27,5 t/ha (yield potential 28,0 t/ha) Ningkay-6 has productivity 24,9 t ha yield potential 28.1 t/ha) and Ordinance Tingkamang-1 has an average productivity of 23.8 t/ha (yield potential of 24.5 t/ha). These three varieties are Ningkay-3, Ningkay-6, and Oringking Tingkamang-1 each also has a very high tuber-dry production either compared to other test varieties or with a comparison variety, the averaged average is 9,3; 8,0 and 7.3 t/ha with dry matter 33.8; 32.3 and 30.8 percent respectively. Further testing with various seasons and more locations and varying altitude is required. Key-words: local clon, sweet potato, Papua